Psychosocial, Eating Behavior, and Lifestyle Factors Influencing Overweight and Obesity in Adolescents. Issue 1 (June 2021) - Agustina, Rina; Meilianawati; Fenny; Atmarita; Suparmi; Susiloretni, Kun A.; Lestari, Wiji; Pritasari, Kirana; Shankar, Anuraj H.
Background: Adolescent overweight and obesity (AOO) is a global public health problem and risk for noncommunicable diseases. Understanding context-specific risks is crucial for interventions. Objective: Determine the prevalence of AOO in the Indonesian National Health Survey (INHS) 2013, assess the 5-year trend from 2013 to 2018, and identify risks. Methods: We selected adolescents aged 10 to 19 years (n = 174 290) from the INHS 2013 and used hierarchical logistic regression to identify gender-specific risks for those aged 15 to 19 years (n = 77 534). Change in AOO was assessed by comparison to INHS 2018 reports. Results: The national AOO prevalence increased over 5 years by 48% in young adolescents (13-15 years) and 85% in older ones (16-18 years). High prevalence areas included the urban location of Jakarta (20.9%) and the remote rural region of Papua (19.4%). Overall, AOO risks were being sedentary, male, lower education, married, younger adolescent, and school enrollment, with urban residence and higher wealth being persistent risks for all analyses. Data for depressive symptoms were available for older adolescents whose additional risks were being sedentary, depressive symptoms, and high-fat diet. Male risks were being sedentary and lower education, and female risks were being married, depressive symptoms, high-fat intake, and lower education. Higher intake of fruits and vegetables and fewer sweets did not protect against AOO if a high-fat diet was consumed. Conclusions: Adolescent overweight and obesity in Indonesia is rapidly increasing, especially in older adolescents and males, and with gender-specific risks. Customized multisectoral interventions to identify strategies for lifestyle change are urgently needed.